Self-Access Centers: Maximizing Learners’ Access to Center Resources - Mark W. Tanner; Neil J. Anderson; Benjamin L. McMurry (Studies in Self-Access Learning Journal, 2010)
Originally published in TESL-EJ March 2009, Volume 12, Number 4 (http://tesl-ej.org/ej48/a2.html). Reprinted with permission from the authors.Although some students have discovered how to use self-access centers effectively, the majority appear to be unaware of available resources. A website and database of materials were created to help students locate materials and use the Self-Access Study Center (SASC) at Brigham Young University’s English Language Center (ELC) more effectively. Students took two surveys regarding their use of the SASC. The first survey was given before the website and database were made available. A second survey was administered 12 weeks after students had been introduced to the resource. An analysis of the data shows that students tend to use SASC resources more autonomously as a result of having a web-based database. The survey results suggest that SAC managers can encourage more autonomous use of center materials by provided a website and database to help students find appropriate materials to use to learn English.